Factors affecting the gravity drainage mechanism from a single matrix block in naturally fractured reservoirs - Mashayekhizadeh, V.; Kamyab, Mohammadreza; Dejam, M.; Ghazanfari, M. (Begell House Inc, 2011)
Despite numerous experimental and numerical studies, fundamental understanding of how the matrix block height, the density difference between petroleum and gas, and matrix capillary pressure could affect the oil recovery from a single matrix block in naturally fractured reservoirs remains a topic of debate in the literature. In this work a one-dimensional gravity drainage model developed by Firoozabadi and Ishimoto (1994) is considered and numerically solved. The Fourier series method is applied for a numerical Laplace inversion of the dimensionless mathematical model; this type of inversion method has rarely been used in petroleum applications. The obtained results revealed that by increasing the matrix block height as well as the density difference between oil and gas, both the drainage flow rate and the cumulative production increased. In contrast, by increasing the matrix capillary pressure, both the drainage flow rate and the cumulative production decreased. The findings of this work can be helpful to better understand the behavior of the gravity drainage process in fractured porous media.